Keragaman Galur-Galur Tomat (Lycopersicon esculentum Mill.) M4 Hasil Irradiasi Sinar Gamma 6O C01 - Nita Damayanti; Rudi Hari Murti; Toekidjo Toekidjo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2007)
-